Beyond audit: Embracing QI methodology to drive improvements in lung‐protective ventilation. Issue 1 (11th November 2021) - Watkin, Daniel; Welhengama, Chamene; Watmore, James; Normanton, Robert; Watson, Joseph; Wallis, Alex; Irvine, Michael; Main, Norman; Crews, Maryam
Abstract: Background: Mechanical ventilation supports patients with respiratory failure during critical illness. Evidence suggests that excessive tidal volumes (regarded as >8 mL/kg predicted body weight [PBW]) cause lung damage through increased lung stretch and alveolar inflammation. Lung‐protective ventilation strategies have been shown to decrease morbidity and mortality, and that all patients should receive tidal volumes between 6 and 8 mls/kg PBW. Despite this, studies demonstrate that fewer than half of patients in critical care successfully receive lung‐protective ventilation. Aim: The primary aim was to reduce tidal volumes delivered to all patients receiving mandatory ventilation, with a target of >85% of tidal volumes delivered to be compliant with lung‐protective ventilation strategies by the end of November 2019. Methods: A multidisciplinary team of nurses and doctors, based in a UK tertiary hospital, utilized the Institute for Healthcare Improvement's (IHI) quality improvement methodology to improve compliance with lung‐protective ventilation. Results: Baseline data demonstrated that only 60.1% of tidal volumes recorded were compliant with lung‐protective ventilation. Quality improvement (QI) methodology was utilized to systematically diagnose the aetiology of poor compliance and to produce and implement solutions. Real‐time data collection and reporting were utilized to monitor and report improvement. Following 8 months of continuous data collection and repeated PDSA cycles, sustainable compliance with lung‐protective ventilation for >85% of tidal volumes was achieved. Conclusions: The use of QI methodology to implement low tidal volume ventilation has shown a significant improvement in the delivery of lung‐protective ventilation. Using QI methodology is central to this sustained improvement and offers a useful tool to systematically approach complex clinical problems. Relevance to Clinical Practice: Lung protective ventilation is critically important in the management of ventilated patients, although compliance in intensive care is variable. Here, we describe how quality improvement methodology can lead to consistent and sustainable improvement in the delivery of lung protective ventilation.